An Underexamined Inequality: Cultural and Psychological Barriers to Men's Engagement With Communal Roles. (November 2015) - Croft, Alyssa; Schmader, Toni; Block, Katharina
Social psychological research has sought to understand and mitigate the psychological barriers that block women's interest, performance, and advancement in male-dominated, agentic roles (e.g., science, technology, engineering, and math). Research has not, however, correspondingly examined men's underrepresentation in communal roles, traditionally occupied by women (e.g., careers in health care, early childhood education, and domestic roles including child care). In this article, we seek to provide a roadmap for research on this underexamined inequality by (a) outlining the benefits of increasing men's representation in communal roles; (b) reviewing cultural, evolutionary, and historical perspectives on the asymmetry in status assigned to men's and women's roles; and (c) articulating the role of gender stereotypes in creating social and psychological barriers to men's interest and inclusion in communal roles. We argue that promoting equal opportunities for both women and men requires a better understanding of the psychological barriers to men's involvement in communal roles.